Low-complexity synchronizer used in OFDM-UWB system - WANG Xue-jing; LIU Liang; YE Fan; REN Jun-yan (Tongxin xuebao)
An efficient synchronizer for OFDM-based UWB system was proposed, which consists of the filter-free symbol synchronizer, frequency synchronizer with improved Moose algorithm and sign-based auto-correlator. According to the results of synthesis using SMIC, 0.13μm CMOS process, the proposed design can achieve the throughput requirement with only 24% gate count and 25% power consumption of the conventional four-parallelism approach.